Study on antioxidants extraction from oak bark and their use for oxidation stability of sunflower oil - Demidova, A. O.; Nosenko, Tamara; Bahmach, Volodymyr; Shemanska, Evgeniya; Molchenko, S. M. (National university of food technologies, 2021)
Food industry requires the antioxidants obtained from natural raw materials. It is important to establish the methods for incorporation of hydrophilic antioxidants to oil and fat products. Materials and methods. Oak bark was used as the raw material for the obtaining of antioxidants. The aqueous-ethanol solutions, alkali and acid addition, and microwave treatment were used for flavonoid extraction. The dry substances content in the extracts was determined gravimetrically. The kinetics of sunflower oil initiated oxidation was studied using a volumetric method in the presence of azobisisobutyric acid dinitrile
Keywords: oak; bark; oxidation; sunflower; oil